Closed Loop Identification by Optimization Method; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Dyadik V. F. Valery Feodosievich (Computation, Automation, Information Technologies and Safety Systems in Nuclear Industry, 2015)
Title screen